The Impact of Learning-language on Students’ awareness of their Identity Lebanon - Zreika, Yosra (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Language is the motto of existence and identity. It is entrusted with preserving the components of nationhood, the richness of the past and an adequate survey of the future. The identity of every nation suggests and endorses the major features of the education and nurturing process. Likewise it defines the basic lines and cultural targets deemed necessary and preferable for the overall operation of teaching and social normalizing. As such, the nature of language and learning become the “mirror” that reflects the identity of the society. This research aims at investigating the impact of the learning-language in consolidating the awareness of the identity, and developing national spirit among students in Lebanon. The research tries to answer the following points: - .What meant by “identity”?What are the challenges that face the “identity” and developing the national spirit among students?Does learning foreign language affect the “identity” ?What is the strategic perception of the convenient learning-language? The research realizes that learning-language must be proficient enough to accompany the spirit of modernization without diminishing the status of the students’ identity. The research adopted the descriptive method to recognize the components of the identity, in addition to using the method of strategic planning to formulate the necessary strategy to preserve the identity. The research relied on samples of volunteers, those who studied in schools where the learning-language is Arabic, and others whose language of learning was foreign. The research adopted a questionnaire distributed among these students. Pertaining to the theoretical side, the research dealt with two parallel lines: the first studied the identity, its concept, components and the challenges that it faces. The second studied the learning-language in teaching institutes, the relation of the identity and language, the ideas of the supporters and opponents of adopting a foreign language as a medium of learning. The research made good reference to other relevant studies. After analyzing the data collected, the research reached certain results and recommendations which support the identity.